2015
DOI: 10.1371/journal.pone.0117597
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Compensation on Health Outcomes following Musculoskeletal Injury: Systematic Review

Abstract: The effect of financial compensation on health outcomes following musculoskeletal injury requires further exploration because results to date are varied and controversial. This systematic review identifies compensation related factors associated with poorer health outcomes following musculoskeletal injury. Searches were conducted using electronic medical journal databases (Medline, CINAHL, Embase, Informit, Web of Science) for prospective studies published up to October 2012. Selection criteria included: progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 77 publications
4
46
0
2
Order By: Relevance
“…2 A recent systematic review concluded that there was an association between compensation (and related factors) and poorer health after a musculoskeletal injury. 29 Since, the NHIS does not capture information on whether individuals received any financial compensation for work- or service-related injuries, we were unable to explore the impact of these variables in our regression model. In particular, it would be informative to compare the prevalence with which Veterans receive compensation for service-related injuries versus compensation for work-related injuries in nonveterans.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent systematic review concluded that there was an association between compensation (and related factors) and poorer health after a musculoskeletal injury. 29 Since, the NHIS does not capture information on whether individuals received any financial compensation for work- or service-related injuries, we were unable to explore the impact of these variables in our regression model. In particular, it would be informative to compare the prevalence with which Veterans receive compensation for service-related injuries versus compensation for work-related injuries in nonveterans.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Murgatroyd et al hypothesized that the effect of receiving WC differed depending on the type of outcome, such as physical function, psychological function, and pain. (14) In their systematic review, they concluded that WC was associated with poorer psychological and physical function results and more pain. However, they were unable to compare outcome types because they did not perform a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Few qualitative studies have identified factors that largely depend on a person's environment and health‐care and compensation systems . Others reported factors such as lack of family support, legal involvement and the compensation claim . However, it is still unclear how these factors impact the recovery outcome; how they interact; and which from an injured person's perspective are the most important to measure to identify people at high risk for poor recovery.…”
Section: Introductionmentioning
confidence: 99%